Teachers' encounter with educational research : an in depth study on the perceived self as language practitioners / Nurulhayati Ilias and Airil Haimi Mohd Adnan - Ilias, Nurulhayati; Mohd Adnan, Airil Haimi (Unit for Research and Intellect Application (UfoRIA), 2009)
Among the six main strategies of Pelan Induk Pembangunan Pendidikan, PIPP 2006-2010, proposed by Ministry Of Education Malaysia and launched by our most respectful Prime Minister on 16 January 2007, is the emphasis on Research and Development R&D to instill research culture among the practitioners. The aim is to upgrade teachers' professionalism and produce empowered teachers to become leaders in our effort to make Malaysia, one of the world class education hubs. Although the teacher-as-researcher movement has been in existence for some twenty years, there is reason to think that the majority of class teachers remain uninvolved. This paper studies school teachers' self perceived as knowledge practitioners and so called 'educators' through their encounter in educational research focusing on their regularity in carrying out these activities: reading/referring to research literature, conducting educational including disseminating findings, writing and publishing academic writing in mass media and teachers' awareness of the co-relationship between research and their professional development. Questionnaires were distributed to 3 schools within the district and few interviews were held to get teachers' in depth personal view towards educational research.